ENHANCING FISCAL TRANSPARENCY AND ACCOUNTABILITY THROUGH IPSAS IN TIMOR-LESTE - Maia, Brandolinda Estela dos Santos; Wijayanti, Nanda Ayu (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study investigates how International Public Sector Accounting Standards (IPSAS) contribute to fiscal transparency and public accountability in post-transitional states, with a focus on Timor-Leste. As a developing nation emerging from a period of transition, Timor-Leste confronts significant obstacles, including limited human resources, policy inconsistencies, and an underdeveloped accounting infrastructure. Employing a qualitative methodology based on a systematic literature review, the research synthesizes findings from academic studies and policy documents to assess how the adoption of IPSAS leads to more comprehensive financial reporting and greater accountability by enhancing the reliability of fiscal information. The study draws on comparative experiences from Portugal, Indonesia, Ghana, and Myanmar to illustrate common challenges and unique outcomes in the implementation of IPSAS. The key contribution of this research is the development of a conceptual framework connecting IPSAS adoption with improved fiscal transparency and accountability in post-transitional contexts. On a practical level, the study offers policy recommendations aimed at bolstering institutional capacity, strengthening human resources, and improving information technology infrastructure—measures crucial for establishing a robust and sustainable system of public financial management.